The Relationship Between Environmental Health Factors and the Incidence of Stunting - Mido Ester J. Sitorus; Ivan Elisabeth Purba; Donal Nababan (PT.Mantaya Idea Batara, 2026)
Background: Stunting is a form of chronic undernutrition that impairs children’s linear growth and development, particularly during the first 1,000 days of life. It remains a major public health problem in many developing countries. Stunting is defined as a length- or height-for-age z-score below −2 standard deviations according to the World Health Organization child growth standards. Environmental health conditions may indirectly contribute to the occurrence of stunting. This study aimed to examine the association between environmental health factors and stunting among children in the working area of the Batang Beruh Health Center, Sidikalang. Methods: This study employed an analytical observational design with a quantitative cross-sectional approach. A total of 64 respondents were recruited using convenience sampling. Data were analyzed using univariate analysis and bivariate analysis with the chi-square test.. Result: Drinking water sources were significantly associated with stunting status (p < 0.001). A significant association was also found between the physical quality of drinking water and stunting (p < 0.001). In contrast, drinking water treatment was not significantly associated with stunting (p = 0.366). Latrine ownership and waste management were significantly associated with stunting status (both p < 0.001). Conclusion: Drinking water sources, the physical quality of drinking water, latrine ownership, and waste management were significantly associated with stunting. However, drinking water treatment was not associated with stunting. Health center personnel should strengthen community education regarding safe water, sanitation, and appropriate waste management practices as part of stunting prevention efforts among children under five.